Antiparasitic Effects of Sulfated Polysaccharides from Marine Hydrobionts - Natalya N. Besednova (MDPI AG, 2021)
This review presents materials characterizing sulfated polysaccharides (SPS) of marine hydrobionts (algae and invertebrates) as potential means for the prevention and treatment of protozoa and helminthiasis. The authors have summarized the literature on the pathogenetic targets of protozoa on the host cells and on the antiparasitic potential of polysaccharides from red, brown and green algae as well as certain marine invertebrates. Information about the mechanisms of action of these unique compounds in diseases caused by protozoa has also been summarized. SPS is distinguished by high antiparasitic activity, good solubility and an almost complete absence of toxicity. In the long term, this allows for the consideration of these compounds as effective and attractive candidates on which to base drugs, biologically active food additives and functional food products with antiparasitic activity.